Gene Targeting to the Uteroplacental Circulation of Pregnant Guinea Pigs. (August 2016) - Mehta, Vedanta; Ofir, Keren; Swanson, Anna; Kloczko, Ewa; Boyd, Michael; Barker, Hannah; Avdic-Belltheus, Adnan; Martin, John; Zachary, Ian; Peebles, Donald; David, Anna L.
Our study aimed to target adenoviral gene therapy to the uteroplacental circulation of pregnant guinea pigs in order to develop a novel therapy for fetal growth restriction. Four methods of delivery of an adenovirus encoding β-galactosidase (Ad.LacZ) were evaluated: intravascular injection using phosphate-buffered saline (PBS) into (1) uterine artery (UtA) or (2) internal iliac artery or external administration in (3) PBS or (4) pluronic F-127 gel (Sigma Aldrich). Postmortem examination was performed 4 to 7 days after gene transfer. Tissue transduction was assessed by X-gal histochemistry and enzyme-linked immunosorbent assay. External vascular application of the adenovirus vector in combination with pluronic gel had 91.7% success rate in terms of administration (85% maternal survival) and gave the best results for maternal/fetal survival and local transduction efficiency without any spread to maternal or fetal tissues. This study suggests an optimal method of gene delivery to the UtAs of a small rodent for preclinical studies.